The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/jgc4.1854
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the occurrence of microaggressions in the genetic counseling student–supervisor relationship: A mixed‐methods study

Kyra Ramsey,
Nikkola Carmichael,
Melissa Gutierrez‐Kapheim
et al.

Abstract: While research has shown that genetic counseling students with minoritized racial or ethnic identities face microaggressions throughout graduate training, quantitative data regarding the frequency of these experiences have not been reported. The purpose of this mixed‐methods study was to investigate the frequency and types of microaggressions experienced by graduates of accredited genetic counseling programs in the United States during fieldwork rotations. A quantitative survey was administered to assess how f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Institutional Review Board (IRB) approval for this study was granted to the first author, K.R., by Northwestern University in 2021. Our (Ramsey et al, 2024). That article offers additional context for the results presented in this paper by describing the scope and characterizing the types of microaggressions study participants reported experiencing.…”
Section: Methodsmentioning
confidence: 93%
“…Institutional Review Board (IRB) approval for this study was granted to the first author, K.R., by Northwestern University in 2021. Our (Ramsey et al, 2024). That article offers additional context for the results presented in this paper by describing the scope and characterizing the types of microaggressions study participants reported experiencing.…”
Section: Methodsmentioning
confidence: 93%